2015
DOI: 10.1016/j.alit.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A workshop with practical training for anaphylaxis management improves the self-efficacy of school personnel

Abstract: Practical instruction of school nurses and school personnel involved with children prescribed an AAI resulted in dramatic improvement of the SE. These people are expected to play a central role in the development of an anaphylaxis management plan in their schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 17 publications
2
24
0
1
Order By: Relevance
“…According to social cognitive theory, perceived efficacy is the foundation of human agency . Many studies support the role of self‐efficacy in different domains of functioning including health management and education . In a previous study, we showed that school personnel had a lower self‐efficacy when asked to manage anaphylaxis, especially in recognizing symptoms and administering proper drugs …”
Section: Introductionmentioning
confidence: 92%
“…According to social cognitive theory, perceived efficacy is the foundation of human agency . Many studies support the role of self‐efficacy in different domains of functioning including health management and education . In a previous study, we showed that school personnel had a lower self‐efficacy when asked to manage anaphylaxis, especially in recognizing symptoms and administering proper drugs …”
Section: Introductionmentioning
confidence: 92%
“…Although the school nurse functions as the leader to coordinate preparation for and response to severe allergic reactions, the US Centers for Disease Control and Prevention (CDC) recommend that all school staff be trained to recognize signs and symptoms of anaphylaxis and to respond appropriately by initiating emergency protocols . Multiple types of educational interventions, including workshops, didactic presentations, and hands‐on demonstrations, have proven to be effective in improving participant knowledge and/or self‐efficacy regarding anaphylaxis identification and management . Achieving self‐efficacy is important because it reflects not only knowledge of the topic, but an individual's belief that he or she is capable of performing the necessary actions—in this case, identifying and appropriately responding to an anaphylactic event.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…25 Multiple types of educational interventions, including workshops, didactic presentations, and hands-on demonstrations, have proven to be effective in improving participant knowledge and/or self-efficacy regarding anaphylaxis identification and management. [26][27][28] Achieving selfefficacy is important because it reflects not only knowledge of the topic, but an individual's belief that he or she is capable of performing the necessary actions-in this case, identifying and appropriately responding to an anaphylactic event. Ideally, training is repeated on a regular basis to maintain competence and confidence.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…A study in Japan evaluated the efficacy of a workshop on anaphylaxis, practical training on how to use an adrenaline auto-injector, and a discussion session. 4 It was found that food allergy education for schoolteachers increased self-efficacy regarding food allergy management at school. 4 Together with the present results, this indicates that food allergy education for schoolteachers would increase self-efficacy regarding management.…”
mentioning
confidence: 99%
“…4 It was found that food allergy education for schoolteachers increased self-efficacy regarding food allergy management at school. 4 Together with the present results, this indicates that food allergy education for schoolteachers would increase self-efficacy regarding management. When presented with the opportunity to educate teachers about food allergy management, we should give due consideration to this factor.…”
mentioning
confidence: 99%